NOVI ET ETERNI TESTAMENTI: UM OLHAR BÍBLICO-DOGMÁTICO SOBRE A MISSA (Razão e Fé, 2021)
This article intends to demonstratethe sacrificial character of Mass, as seen onExodus’s chapter 12 and it’s depictment of theestablishment of Easter, in which it’s seen theimage of the immolated lamb who keeps deathat bay and prepares the liberation of the hebrewfrom the house of slavery. It also analyses, withthe same objective, the texts regarding theformation of the New Alliance in the Last Supperthat Jesus shared with the Apostles and thenarrative of the Passion, by which Our Lord, theLamb of God who takes away the sin of the world,completed the work of redemption and freedmen from the servitude of sin. Lastly, we turn ourgaze towards some contemporary ecclestialmagistery’s documents, where we intendedto find doutrinary and dogmatic elementsregarding the Mass and how the actualizationof the Cross’s sacrifice takes place through theactions of the Church, Mystic Body of Christ.